Das Ziel der grossen Reise Alexander von Humboldts - Beck, Hanno (ERDKUNDE, 1958)
The introduction to this paper is devoted to the importance of a stage of preparation in the history of travel. From the middle of the 18th century onwards the value of a thorough preparation became increasingly recognized; the voyages of Bougainville, Cook and Malaspina were as equally well prepared as the travels of Carsten Niebuhr, Peter Simon Pallas and Samuel Georg Gmelin. Humboldt in his youth was well acquainted with expeditions, but so far it has not been possible to establish whether he had any well-defined aim for his journey for which he carried out thorough preparations. Thus the question which is posed in this paper is first and foremost: Did Humboldt have a particular aim for which he prepared himself accordingly? During 1796-97 Humboldt made the acquaintance of the brothers Keutsch, medical students from the then Danish island of St. Thomas in the West Indies. They studied at Jena and Humboldt collaborated with them and planned to accompany them to the West Indies in order to commence his investigations there. He then prepared himself extremely thoroughly for his journey, particularly by means of published material and generally by intensified scientific studies and frequent practice in the use of the best surveying instruments at his disposal. Before 1799 this kind of preparation was without a parallel. In 1797 Humboldt spent the months of August to October in Vienna where, in Nikolaus Jacquin and Franz Boos he got to know two of the most important Austrian West Indies travellers. It was then that Humboldt realised that the three Austrian expeditions which had been sent to the West Indies during the period from 1755?88, mainly to enrich the plant collection of the botanical gardens of Schonbrunn, had been amongst the most important under takings in the history of travel. In the botanical gardens of Schonbrunn he was able to study a great number of West Indian plants. These facts show that Humboldt had a clear aim for his journey, which was suggested by the brothers Keutsch, and further influenced by the facilities for study in Vienna, then the largest German metropolis. Only his preparations in general and, in particular in respect of the aims of his travel to the West Indies, explain why the beginning of his great journey in 1799 is such an important landmark in the history of travel.